Investigation of Electrical, Acoustical and Optical Properties of Nanopowder Dispersed Cholesteric Liquid Crystal - Mani, Santosh; Patwardhan, Suren; Khosla, Samriti; Sarawade, Pradip (Recent Trends in Chemical and Material Sciences Vol. 5, 2022)
The composite materials based on nanopowder dispersed liquid crystals are important both from fundamental research and device applications due to their unique properties such as improvement in various properties like electrical, optical, thermal, energy storage and spontaneous polarization etc. The proper selection of nanoparticle and its size which to be dispersed in particular liquid crystals is very important for a particular application. In the present study, a ferroelectric nanopowder of Barium Titanate (BaTiO3) was dispersed in cholesteric liquid crystal and the same was confirmed by Fourier Transform Infrared (FTIR) Spectroscopy. The various acoustical properties like ultrasonic velocity, density, Adiabatic Compressibility, Rao Constant, Wada Constant and Acoustic Impedance were investigated by ultrasonic interferometer at room temperature at fixed frequency. The dielectric constant was determined by Precision Impedance Analyzer. In addition to these investigations, particle size and surface area were also measured. Our investigation shows enhanced in dielectric and acoustical properties which may be useful for device applications extensively in microelectronics, low cost- photovoltaic devices, and custom-shaped containers possibly applied as a coating. The sensitivity of Liquid Crystal is enhanced after dispersing ferroelectric nanopowder which increases the performance of the Liquid Crystal.